2012
DOI: 10.1508/cytologia.77.453
|View full text |Cite
|
Sign up to set email alerts
|

Crossability of <i>Brassica carinata</i> and <i>B. tournefortii</i>, and Cytomorphology of Their F<sub>1</sub> Hybrid

Abstract: Summary Reciprocal crosses between Brassica carinata (BBCC, 2n=34) and B. tournefortii (TT, 2n=20) were attempted in order to determine crossability between the species, carry out chromosomal associations among the B, C and T genomes, and to study morphology of the interspecific hybrids. A hybrid between these 2 species was obtained only when B. carinata was used as a female parent. Morphologically, the hybrid was intermediate between the progenitor species but its leaves resembled B. carinata. The F 1 plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
4
3
0
Order By: Relevance
“…The F 1 hybrid plants thus obtained were observed to be intermediate in terms of many phenotypic features of both the parents. These observations are in congruence with earlier published reports (Chen et al 2011, Choudhary andJoshi 2012). The occurrence of characteristics from both progenitor species in the hybrids indicates that the F 1 plants inherited genomes of both parental species crossed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The F 1 hybrid plants thus obtained were observed to be intermediate in terms of many phenotypic features of both the parents. These observations are in congruence with earlier published reports (Chen et al 2011, Choudhary andJoshi 2012). The occurrence of characteristics from both progenitor species in the hybrids indicates that the F 1 plants inherited genomes of both parental species crossed.…”
Section: Discussionsupporting
confidence: 92%
“…Occasional laggards were recorded at anaphase I and II. Unequal distribution of chromosomes at anaphase I were recorded in few cells and in anaphase II few PMCs with laggards and one cell intermixing of chromatids at one pole was also encountered, it is similar to the study reported by Choudhary and Joshi (2012). Decrease in pollen fertility and reduced seed set recorded in the present hybrids might be due to meiotic irregularities and segregational anomalies (Singh 1993).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Unequal distribution of chromosomes at anaphase I was recorded in a few cells, which is similar to the study reported by Choudhary and Joshi (2012). The drastic decrease in pollen fertility and reduced seed set recorded in the present hybrids might be due to meiotic irregularities and segregational anomalies (Singh 1993).…”
Section: Discussionsupporting
confidence: 91%
“…In this research, no relationship between characteristics of the pollen grains and meiosis or molecular results was observed. Similarly to other experiments, pollen viability was much lower in F1 hybrids than in the two parental species (Pertl et al, 2002, Choudhary & Joshi 2012. However, different shape of pollen grains did not affect the grains' viability.…”
Section: Discussionsupporting
confidence: 79%